Osmolar gap with Minimal Acidosis in Combined Methanol and Methyl Ethyl Ketone Ingestion - Price, E. A.; D'alessandro, A.; Kearney, T.; Olson, K. R.; Blanc, P. D. (Journal of toxicology. Clinical toxicology, 1994)
Methyl ethyl ketone is a common solvent but data on overdose in humans are scarce. We report a case of co-ingestion of methyl ethyl ketone together with methanol associated with a hyperosmolar coma without anion gap metabolic acidosis. Blood levels of methyl ethyl ketone and its metabolite, 2-butanol, indicated that this solvent did contribute approximately 20 mosm/L to an observed osmolar gap of 99 mosm/L. At the levels detected, methyl ethyl ketone may have inhibited methanol metabolism, contributing to the low serum formate (1.3 mmol/L) and normal anion gap despite a blood methanol of 67 mmol/L.